Parental morphine exposure enhances morphine (but not methamphetamine) preference and increases monoamine oxidase-B level in the nucleus accumbens. Issue 5 (August 2019) - Sadat-Shirazi, Mitra-Sadat; Karimi, Forough; Kaka, Gholamreza; Ashabi, Ghorbangol; Ahmadi, Iraj; Akbarabadi, Ardeshir; Toolee, Heidar; Vousooghi, Nasim; Zarrindast, Mohammad-Reza
Abstract : Opioid addiction is one of the most crucial issues in the world. Opioid abuse by parents makes children more prone to many psychological disorders such as drug addiction. Therefore, this study was carried out to examine the effect of morphine exposure 10 days before gestation on morphine and methamphetamine preference in male offspring. Adult Wistar rats (male and female) received morphine orally for 21 days and were drug free for 10 days. Thereafter, they were allowed to mate with either a morphine-abstinent or drug-naive rat. The male offspring were tested for morphine and methamphetamine preference with a three-bottle choice test. Moreover, the rewarding effects of morphine and methamphetamine were evaluated using a conditioned place preference test. To determine the mechanisms underlying these changes, monoamine oxidase-B (MAO-B) level was measured in the nucleus accumbens (NAC). Offspring of morphine-abstinent mothers and offspring of both-abstinent parents were found to consume morphine more than those of other groups, but in the case of methamphetamine, there were no differences. In addition, the offspring of morphine-abstinent parent(s) did not condition with a high dose of morphine in the conditioned place preference test. Administration of methamphetamine induced conditioning at different doses in controls and offspring of one or two morphine-abstinent parent(s), and there were no effects of parental morphine exposure on the dose of methamphetamine that was required for conditioning. Moreover, the level of MAO-B was increased in the NAC of offspring of morphine-abstinent parents as compared with the control group. These results demonstrate that offspring of a morphine-abstinent mother and a drug-naive father and offspring of two morphine-abstinent parents were more susceptible to opioid but not methamphetamine addiction. Moreover, parental morphine consumption did not have any effect on the reinforcing effect of methamphetamine in their offspring but induced morphine tolerance in the offspring. Although the level of MAO-B was elevated in the NAC, this did not correlate with the methamphetamine preference in offspring.